Journey through the writing process: Metaphors of thesis writing experience - Hanić, Jasmina; Pavlović, Tanja; Jahić Jašić, Alma (ExELL, 2025)
This paper aimed to investigate metaphorical images used by master’s students in order to gain an insight into their schemata for thinking about the process of master’s thesis writing. Semi-structured interviews on the topic of master’s thesis writing with three students coming from humanities, social sciences and natural sciences served as a corpus from which the data were extracted. The paper analysed participants’ unconscious use of metaphorical language in their narratives, mirroring their perception of the thesis writing process. The results revealed that the participants’ personal experience revolves around the concept of journey as the central image they share and the journey metaphor, along with a group of related specific metaphors, serves to illustrate the complexity of the writing process itself.